Internationalization: An Analysis of 26 Definitions - López Morales, José Satsumi (Intersticios Sociales, 2020)
There are many definitions related to the term “internationalization.” This article will analyze 26 of the term’s definitions as identified in the literature. Four dimensions of internationalization were identified in the literature: (1) Uppsala model (UM); (2) eclectic paradigm (EP); (3) depth; and (4) breadth. A qualitative technique of content analysis was implemented to analyze the 26 definitions. The main results suggest that depth is the most frequent dimension (20), followed by UM and EP (16), and breadth (12). Only two definitions included all four dimensions. The article concludes that internationalization is a complicated phenomenon with several approaches and is difficult state an unique definition.